Effectiveness of Social-Psychological Service in the Prevention of Adolescents with a Difficult Education - Abdukakhorova Gulnoza Abdurasulovna (International Journal on Integrated Education, 2022)
Legal documents are important for teachers and psychologists in practical work with adolescents with deviant behavior and difficult upbringing. The practical aspects of social-psychological service in conducting psychoprophylactic work on the problem of deviant behavior in adolescents are highlighted.